Cities of the Dawn : Naples - Athens - Pompeii - Constantinople - Smyrna - Jaffa - Jerusalem - Alexandria - Cairo - Marseilles - Avignon - Lyons - Dijon - Ritchie, J. Ewing (James Ewing), 1820-1898 (Salt Lake City, UT : Project Gutenberg, 2011)
"Cities of the Dawn" by J. Ewing Ritchie is a historical novel written in the late 19th century. The narrative begins in the early 1800s and revolves around two travelers making their way through France. The focal point appears to be on their journey, as well as the social and political landscape of the time, hinting at underlying tensions and mysteries related to the historical context of the French Revolution and its aftermath. The opening of the narrative introduces us to the characters of two travelers who are navigating the landscape of post-revolutionary France. They arrive in a small town and engage with the local innkeeper, who seems to be aware of the dangers that lurk in the surrounding regions. The travelers, while initially focused on their immediate needs$1 (Btheir hunger and thirst$1 (Bbecome embroiled in discussions about their continuing journey toward Mirecourt, a location that appears to carry with it a sense of foreboding. As they converse, elements of camaraderie and a hint of intimacy are established, particularly in the exchange between one traveler$1 (Bidentified as Philippe Hattier$1 (Band the mysterious marquis, signaling that their fates may be intertwined in ways they do not yet realize. This sets the stage for a tale steeped in suspense, mystery, and the consequences of the political upheaval affecting their lives. (This is an automatically generated summary.)s
A run across France -- Off to Naples -- Naples of to-day -- Pompeii and Vesuvius -- The isles of the Mediterranean -- About Athens -- Constantinople -- Smyrna -- Jaffa to Jerusalem -- The Holy City -- Bethlehem -- The Jew in Jerusalem -- Alexandria -- In Cairo -- The pyramids and the Sphinx -- The river Nile -- The return to Marseilles -- Avignon -- The great city of Lyons -- Dijon, or the wine country -- Books of reference.
Release date is 2011-05-11
Transcribed from the 1897 T. Fisher Unwin edition by David Price
Keywords: Travel; Cities and towns, Ancient; Mediterranean Region -- Description and travel